Comparative politics explaining democratic systems - Bara, Judith; Pennington, Mark 1970-.; Bell, David Scott (Los Angeles, [Calif.] London SAGE, 2009)
This text provides an introduction to the study of comparative politics. Rich in case study material and global in coverage, it sets out the basic theoretical and methodological foundations for studying different political systems as well as the key structures and actors of which they are comprised.
Keywords: Comparative government; Representative government and representation